Empire in Crisis: Gothic Invasions and Roman Historiography (2020)
The volume, which has emerged from an international conference of the same title, unites a range of disciplinary and interdisciplinary contributions on invasions of Goths and other Germanic tribes into the Roman Empire, focusing primarily on the third-century CE. The newly discovered fragments of the lost work Scythica by the third-century historian Dexippus of Athens, the so-called Scythica Vindobonensia alias Dexippus Vindobonensis, which survived in a Greek palimpsest kept in the Austrian National Library in Vienna, have great impact on the study of this field. The contributions explore the Vienna fragments in their historical and historiographical contexts, from the Roman to the Byzantine Era, and the history of the invasions themselves.